2020
DOI: 10.37934/cfdl.12.12.5562
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Inlet Velocity on Cooling Speed in a Refrigerated Container using CFD simulations

Abstract: The use of refrigerated containers continues to increase rapidly in line with global trade, this kind of container is commonly used to deliver perishable cargo from producers to consumers over great distances, even between continents. To avoid perishable goods from damages, the temperature inside refrigerated containers was controlled and maintained to keep the cooling performance. The purpose of this study is to investigate the effect of variation inlet velocity on the cooling speed inside a refrigerated cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…6 to 8 present the temperature values for the outdoor and indoor temperature obtained via the data logger during the over-all five-day period and the artificial neural network predictions for the indoor temperature. The study has shown that there need to conserve energy consumption by using a PU roofing system, which is in line with the study of [23][24][25]. The authors surveyed the alternative application of nanoparticles in increasing the cooling rate within the house environment for human comforts.…”
Section: Results Of Ann Prediction Analysis Of Pu-al Roofing Systemsupporting
confidence: 67%
“…6 to 8 present the temperature values for the outdoor and indoor temperature obtained via the data logger during the over-all five-day period and the artificial neural network predictions for the indoor temperature. The study has shown that there need to conserve energy consumption by using a PU roofing system, which is in line with the study of [23][24][25]. The authors surveyed the alternative application of nanoparticles in increasing the cooling rate within the house environment for human comforts.…”
Section: Results Of Ann Prediction Analysis Of Pu-al Roofing Systemsupporting
confidence: 67%
“…Table 5 summarizes all the data from the thermal analysis. Inlet velocity influence on the temperature was neglected although results shown inlet velocity speed affects the cooling [19]. While epoxy is supposedly thermally resilient, grey cast iron had shown better results than carbon fibre in terms of the manifold and air temperature.…”
Section: Thermal Analysismentioning
confidence: 99%
“…In the application of the CFD method on reefer containers [17,18], there are several aspects that need to be considered, one of which is the placement of the skipjack tuna which is formed in packages on pallets. Another thing that needs to be considered is the area inside the pallet fish packaging to the wall requires a perfect arrangement, this aims to avoid cells or tilted arrangements.…”
Section: Introductionmentioning
confidence: 99%